2019
DOI: 10.1039/c9sc03248g
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-controlled electrospray ionization mass spectrometry as a tool to study collagen homo- and heterotrimers

Abstract: Temperature-programmed native electrospray ionization mass spectrometry gives detailed insight into the assembly of model collagen triple helices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 47 publications
1
36
0
1
Order By: Relevance
“…The duplex is denatured at 55 ± 1°C. Both thermal denaturation temperatures are very similar to those obtained by CD when monitoring specific wavelengths as previously demonstrated for other DNA complexes 10 and for collagen triple helices 63 (21°C at 269 nm and 53°C at 242 nm for the triplex-duplex and duplex-monomer transitions, respectively; Supplementary Fig. 12).…”
Section: Resultssupporting
confidence: 84%
“…The duplex is denatured at 55 ± 1°C. Both thermal denaturation temperatures are very similar to those obtained by CD when monitoring specific wavelengths as previously demonstrated for other DNA complexes 10 and for collagen triple helices 63 (21°C at 269 nm and 53°C at 242 nm for the triplex-duplex and duplex-monomer transitions, respectively; Supplementary Fig. 12).…”
Section: Resultssupporting
confidence: 84%
“…Protein melting (El‐Baba et al, 2018) or thermal heating of the solution (Wang, Bondarenko, & Kaltashov, 2018; Kohler et al, 2019) within the ESI emitter provide new approaches for determining the thermal stabilities of peptides, proteins, and even protein complexes. The combination of VT‐ESI with IM‐MS affords the ability to investigate structural transitions (refolded states) of biomolecules by kinetically trapping folding intermediates in the gas phase.…”
Section: Folding/refolding Proteins In Solution Using Vt‐esimentioning
confidence: 99%
“…The breadth of the studies described above clearly illustrate the unique potential for CIU, VT‐ESI‐IM‐MS, and MS/MS for studies of complex protein systems; however, incorporating additional MS‐based structural approaches adds to the biophysical characterization of proteins and protein complexes and their labeling with covalent and/or noncovalent modifiers. As examples, our current level of understanding of the structure(s) of partially metalated metallothionein comes from combining covalent labeling of the cysteine side chains with N ‐ethylmaleimide (Kohler et al, 2019) with top‐down and bottom‐up proteomics approaches (Chen, Russell, & Russell, 2013; Chen & Russell, 2015b).…”
Section: Combining Ciu and Vt‐esi‐im‐ms To Probe Stabilities Of Protementioning
confidence: 99%
“…[55] Contrary to CD,m ass spectrometry requires ionization and transfer of molecules into the gas phase where they are detected usually with an electron multiplier type detector.Our group recently demonstrated that native MS coupled with temperaturecontrolled nanoelectrospray (TCnESI) source is au seful analytical tools for structural biology and can retrieve detailed thermodynamic data on non-covalent complexes of peptides,p roteins,a nd oligonucleotides. [56,57] MS can be beneficial in studies focusing on multi-domain oligonucleotide complexes where the number of potential intermediates is unknown or the intermediates occur at low abundance.…”
Section: Introductionmentioning
confidence: 99%